Optimizing Corporate Social Resposibility for Enhanced Economic Resilience: An Accounting Perpective - Mareta, Sigit; Doktoralina, Caturida Meiwanto; Lestari, Lestari; Dewi, Ranita Puspita Sari; Christsetyo, Peter Azarya Misael Andrew (Business, Management & Accounting Journal (BISMA), 2024)
Environmental CSR plays an urgent role in supporting the economic resilience of coastal communities, where livelihoods are deeply intertwined with natural resources. However, the full potential of CSR in these regions has not yet been optimised due to challenges in both environmental management and financial transparency. Coastal communities remain vulnerable to economic fluctuations, making it essential to understand how CSR initiatives can enhance long-term stability. This paper examines the theoretical model of Environmental CSR and financial transparency, exploring how these factors can strengthen the economic resilience of coastal communities. By integrating environmental conservation efforts with transparent financial reporting, CSR can empower communities to manage their resources sustainably and reduce dependency on external forces.  This study is one of the few addressing CSR's role in coastal regions, particularly in the context of environmental sustainability and financial management. The findings are expected to provide valuable insights for both academic research and practical policy-making, offering a framework for enhancing CSR effectiveness in vulnerable areas. Ultimately, this research aims to contribute to sustainable economic development and community resilience, with a specific focus on coastal regions.